CHARTING THE COURSE: AN OVERVIEW OF PHARMACOVIGILANCE HISTORY - Lalit Sharma; Nancy Vaid; Himanshu; Tanuj; Mohit (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Pharmacovigilance is a critical component of healthcare systems worldwide, focusing on the detection, assessment, understanding, and prevention of adverse effects or any other drug-related problems. This abstract provides a concise overview of pharmacovigilance, its significance, objectives, and key processes. It highlights the role of pharmacovigilance in ensuring the safety and efficacy of pharmaceutical products and its evolving importance in the context of public health. It also emphasises the international collaboration and legal framework that oversee pharmacovigilance efforts, highlighting the ongoing requirement for thorough medication safety monitoring to safeguard patient welfare.